1998
DOI: 10.1164/ajrccm.157.5.9707113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Route of Breathing on Response to Exposure in a Swine Confinement Building

Abstract: Exposure of naive subjects to swine buildings results in acute nasal, lung, and peripheral blood inflammatory responses with an increase in nonallergic airway responsiveness. Because nasal passages filter large particles and soluble gases and because swine building exposure results in an acute inflammatory response at this level, we questioned what effect breathing through or avoiding this route would have on local and systemic inflammation. Nine normal young men 23 to 37 yr of age were exposed for 5 h to a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…26 This study confirms that working in swine confinement buildings results in cross-shift decline in lung function and increases blood neutrophils and IL-6. In contrast to previous studies with subjects naive to the environment 10,12,27 (where circulating TNF levels either increased or remained constant at high concentrations), plasma TNF stayed at low concentrations and tended to decrease further during both visits. This could be an indication of a difference in the immune reactions between a first time exposure and repeated exposures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…26 This study confirms that working in swine confinement buildings results in cross-shift decline in lung function and increases blood neutrophils and IL-6. In contrast to previous studies with subjects naive to the environment 10,12,27 (where circulating TNF levels either increased or remained constant at high concentrations), plasma TNF stayed at low concentrations and tended to decrease further during both visits. This could be an indication of a difference in the immune reactions between a first time exposure and repeated exposures.…”
Section: Discussioncontrasting
confidence: 99%
“…10,11 Increases in tumor necrosis factor (TNF) have been found in some 4 but not in all studies, 12 but downstream effects of TNF release probably also depend on the concentration of its receptors. The TNF receptors have been shown to increase locally following bronchial endotoxin instillation in humans.…”
Section: S Ince the Early 1980s Numerous Studies Have Demonstrated Lumentioning
confidence: 99%
“…It is presently not clear which of these substances or if their combination is responsible for the health effects of SCB. It has recently been shown that nasal filtration did not prevent lung and systemic effects of swine confinement building air, suggesting that small respirable particles are involved [18]. Canola oil spray offers significant protection; the exact effect of spraying oil on the quality of the air in SCB has however not been determined [19].…”
mentioning
confidence: 99%
“…In the agricultural setting, inhalation exposure to high concentrations of mixed organic dusts, which contain bacteria, fungi, endotoxins, glucans, and mycotoxins, has been associated with organic toxic syndrome and acute febrile illness. Cormier et al [1988] showed increased interleukin-6 and -8 levels in nasal washes after exposure in a swine confinement building.…”
Section: Discussionmentioning
confidence: 99%